Abnormalities in exercising skeletal muscle in congestive heart failure can be explained in terms of decreased mitochondrial ATP synthesis, reduced metabolic efficiency, and increased glycogenolysis. Issue 1 (July 1996) - Kemp, G. J.; Thompson, C. H.; Stratton, J. R.; Brunotte, F.; Conway, M.; Adamopoulos, S.; Arnolda, L.; Radda, G. K.; Rajagopalan, B.
Abstract : OBJECTIVE: To distinguish between the effects of reduced oxidative capacity and reduced metabolic efficiency on skeletal muscle bioenergetics during exercise in patients with congestive heart failure. DESIGN AND PATIENTS: Patients were studied by 31P magnetic resonance spectroscopy during aerobic exercise and recovery, and results compared with controls. RESULTS: In flexor digitorum superficialis muscle (26 patients) there was a 30% decrease in oxidative capacity compared with control (mean (SE) 36 (2) v 51 (4) mM/min) and also a 40% decrease in "effective muscle mass" (5 (1) v 9 (1) arbitrary units), probably at least partly the result of reduced metabolic efficiency. Both contribute to increased phosphocreatine depletion and intracellular acidosis during exercise. However, an increased concentration of ADP (an important mitochondrial regulator) during exercise permitted near-normal rates of oxidative ATP synthesis. Results were similar in gastrocnemius muscle (20 patients), with a 30% decrease in maximum oxidative capacity (29 (4) v 39 (3) mM/min) and a 65% decrease in effective muscle mass (5 (1) v 13 (2) arbitrary units). Exercise training improved maximum oxidative capacity in both muscles, and in gastrocnemius effective muscle mass also. CONCLUSIONS: Skeletal muscle exercise abnormalities in patients with congestive heart failure results more from decreased metabolic efficiency than from the abnormalities in mitochondrial oxidation. Both decreased efficiency and defective mitochondrial oxidation result in an increased activation of glycogen phosphorylase, and may be improved by exercise training.